A systematic review and meta-analytic synthesis of the relationship between compulsory citizenship behaviors and its theoretical correlates - Yildiz, Bora; Kaptan, Zeynep; Yildiz, Tayfun; Elibol, Esengul; Yildiz, Harun; Ozbilgin, Mustafa (Frontiers in Psychology, 2023)
Background Compulsory citizenship behaviors (CCBs) are increasingly endorsed and expected of workers in contexts where managerial worker protections are low and performance demands on workers are high. Although studies on compulsory citizenship behaviors have shown a significant increase in recent years, the literature still lacks a comprehensive meta-analysis. To fill this gap the purpose of this study is to synthesize the collective outcomes of prior quantitative research on CCBs with the objective of identifying the factors linked to the concept and offering a primary reference for future researchers. Methods Forty-three different correlates with CCBs were synthesized. The dataset of this meta-analysis consists of 53 independent samples with a sample size of 17.491, contributing to 180 effect sizes. PRISMA flow diagram and PICOS framework were used for the study design. Result Results showed only gender and age were significant among demographic characteristics related to CCBs. Correlates between CCBs and counterproductive workplace behaviors, felt obligation, work-family conflict, organizational-based self-esteem, organizational cynicism, burnout, anger toward the organization, and work alienation were found as large. We also found turnover intention, moral disengagement, careerism, abusive supervision, citizenship pressure, job stress, facades of conformity, and feeling trusted to be moderately related to CCBs. Next, there was a small relationship between CCBs and social loafing. On the other hand, LMX, psychological safety, organizational identification, organizational justice, organizational commitment, job satisfaction, and job autonomy were found as significant deterrents of CCBs. These results suggest that CCBs flourish in contexts with low levels of worker protection and low road practices to people management. Conclusion In sum, we found solid cumulative evidence that CCBs are a harmful and undesirable phenomenon for employees and organizations. Also, positive correlations of felt obligation, feeling trusted, and organization-based self-esteem with CCBs, showed that, contrary to general acceptance, positive factors could also cause CCBs. Lastly, we found CCBs as a dominant phenomenon in eastern culture.